The Funambulist Pamphlets 6 Palestine (Punctum Books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist, collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.